Surgical treatment of severe laryngomalacia: Six month follow up. Issue 6 (21st September 2015) - Baljosevic, Ivan; Minic, Predrag; Trajkovic, Goran; Markovic‐Sovtic, Gordana; Radojicic, Bojana; Sovtic, Aleksandar
Abstract: Background: Laryngomalacia (LM) is the most common congenital anomaly of larynx that causes stridor in children. We evaluated the efficacy of epiglottic suture and laser epiglottopexy for treatment of infants with severe LM. Methods: Surgical intervention was performed in 19 patients with severe LM, after the diagnosis was established using flexible laryngotracheobronchoscopy. Five patients had isolated type 1 LM, and 14 patients had a combination of type 1 and 3 LM. Indication for surgical treatment was the presence of LM with at least one of the following: malnutrition (body mass index [BMI] Z score < –2 SD), dysphagia or symptoms of gastroesophageal reflux and mean oxygen saturation (SaO2 ) <92% with oxygen desaturation index (ODI) > 3. Results: Epiglottic suture was performed in 11 patients, and laser epiglottopexy in eight, at mean age 3.95 ± 2.4 months. Rate of operation was 2.2‐fold greater for more severe anomaly (combination of type 1 and 3 LM) than for isolated type 1. At 6 month follow up symptoms had gradually improved, as well as nutritional status, with increase of mean BMI Z score from –3.7 to –0.9 ( P < 0.01). Mean preoperative SaO2 was 89.4 ± 4.3% with mean ODI of 5.8. At 6 month follow up, mean SaO2 was 96.7 ± 1.1%, and mean ODI was 1.2 ( P < 0.01). Conclusions: Epiglottic suture and laser epiglottopexy are efficient surgical techniques that lead to significant improvement of symptoms, oxygenation and nutritional status in patients with LM.